PRODUCING, STORAGE AND PROCESSING OF MELONS USING MODERN RESOURCE-SAVING TECHNOLOGIES - Nishonova Asal Yakubjonovna; Joraev Urol Chorievich; Mokhinur Khasanova; Zokirov Kurbonalijon Gaybullo ogli (Journals Park Publishing, 2022)
In this article, the results of the research carried out in the field of cultivation, storage and processing of rice crops using modern resource-saving technologies are written with an in-depth scientific analysis. Also, the article provides scientific conclusions and advice for production industries.
Keywords: melon, watermelon, variety, hybrid, seedling, phenophases, drip irrigation, mulching.